Ibrutinib for the treatment of mantle cell lymphoma. Issue 5 (October 2014) - Shah, Nimish; Hutchinson, Claire; Rule, Simon
<x xml:space="preserve">Abstract</x> Mantle cell lymphoma (MCL) is a rare and aggressive form of non-Hodgkin's lymphoma. It can follow a heterogeneous clinical course but generally patients relapse early after standard immunochemotherapy regimens and develop resistance to subsequent therapies. For younger patients, intensive approaches followed by autologous stem cell transplantation offer excellent long-term disease control but with the possible exception of an allogenic stem cell transplant, MCL is an incurable condition. As MCL principally affects older individuals, the majority of patients are not candidates for such intensive approaches. Ibrutinib is an orally active, Bruton's tyrosine kinase inhibitor. It inhibits signaling pathways downstream of Bruton's tyrosine kinase that appear critical for the proliferation and survival of MCL. As a single agent it has shown extremely promising activity in relapsed and refractory MCL patients with an excellent side-effect profile. The exact role for ibrutinib in the treatment of MCL is yet to be established; however, it is likely to fundamentally change the way we treat this disease.